GAYA HIDUP MASYARAKAT PASCAMODEREN - Kistanto, Nurdien Harry (Fakultas Ilmu Budaya Universitas Diponegoro, 2016)
Indonesians are undergoing a socioeconomic transformation from a agricultural society to an industrial society. In the transformation, Indonesian postindustrial society shifts to postmodern society. The postindustrial society is theoretically designated as information society, knowledge economy, post-industrial economy, and network society. In the meantime, the postmodern society is designated with uncertainty, insecurity, and doubt. The lifestyle of the agricultural society is accordingly merged with that of the postmodern society. A class system is present in the agricultural society and in the postmodern society, and the middle class is dominant in between the societies. This essay presents the growth, the shopping pattern and the life style of the middle class. The shopping pattern comprises domestic consumption, technology awareness, banking, and telecommunication sector, food and drinks, and minimarkets. In all, the transformation brings about the mixture between the two societies.